3001 : The Final Odyssey - Clarke, Arthur C. (London : HarperCollins, 1997)
The body of Frank Poole, murdered by mad computer HAL a thousand years earlier, is found and revived to a world of peace and plenty, but in this attempt to understand the entity composed of his farmer deputy Dave Bowman and a copy of the now-sane HAL,Frank learns that Earth is slated for destruction.
Keywords: Computers -- Fiction; Life on other planets fiction; Science fiction